PROBLEMS CONCEPTS AND EVIDENCE OF A CRIME IN ISLAMIC LAW - Turgumbayev, Марлен Ерланович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The article examines the definition of a crime under Islamic law. Development of the theory of crime in Islamic law is carried out based on two fundamental philosophical and theological principles: all actions and thoughts of people anyway, predetermined by the will of Allah and consideration as a crime of disobedience of Allah. This approach affects the entire Muslim criminal law concept, which uses a broad understanding of the crime as a serious sin, combined with its narrow definition in the formal legal sense and leads to the dual nature of the legal consequences of the offense.